Lead brass and preparation method thereof

By adjusting the chemical composition and structure of lead brass, the problem of C3601 lead brass cracking during cold heading forming and bending is solved, and the higher crack resistance and cutting performance are achieved, ensuring the processing quality of the valve nozzle and vehicle safety.

CN119433282APending Publication Date: 2025-02-14JINTIAN COPPER GROUP CORP NINGBO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411601745.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing C3601 lead brass is prone to cracking during cold heading forming and bending, which affects the processing quality of the valve and the driving safety of the vehicle.

Method used

By adjusting the chemical composition of lead brass, the Cu content is controlled at 60.0-63.0 wt%, the Pb content is 1.1-2.6 wt%, the Fe content is ≤0.04 wt%, the Al content is ≤0.06 wt%, and the Sn content is ≤0.1 wt%, and 15-30% twins are formed in the tissue, and the distribution of β-phase and Pb phase is optimized to improve the cold heading and bending properties of the material.

Benefits of technology

It significantly improves the cold heading cracking and bending cracking resistance of lead brass, ensures the processing quality of the valve and the safety of the vehicle, while maintaining good cutting performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433282A_ABST
    Figure CN119433282A_ABST
Patent Text Reader

Abstract

The invention discloses lead brass and a preparation method thereof. The lead brass comprises the following components in percentage by mass: 60.0-63.0 wt% of Cu, 1.1-2.6 wt% of Pb, less than or equal to 0.04 wt% of Fe, less than or equal to 0.06 wt% of Al, less than or equal to 0.1 wt% of Sn and the balance of Zn, the structure of the lead brass comprises twin crystals, and the twin crystals account for 15-30% of the area of the lead brass. The lead brass has better cold heading cracking resistance and bending cracking resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brass, and in particular relates to lead brass and a preparation method thereof. Background Art

[0002] The valve is an independent valve body device, a small component used to inflate and deflate the tire. It is usually made of metal or other materials and has different shapes and sizes. The main function of the valve is to inflate the vehicle tire when needed, or to release air when not needed, so as to keep the tire pressure within the appropriate range. The valve is a key component to ensure the normal operation of the tire and driving safety.

[0003] The existing valve processing technology: brass wire → cold heading → thread rolling → CNC center processing → annealing → bending. The processing flow involves cold heading, cutting, bending and other processes, and has high requirements on the cold heading performance, cutting performance and bending performance of copper materials. In the existing technology, C3601 lead brass alloy is mostly used as the material of brass wire.

[0004] C3601 lead brass is a Pb-containing brass alloy with excellent properties. It has good cutting and drilling performance, is easy to drill, has good ductility and toughness, can withstand cold and hot pressure processing, and is suitable for automatic lathes and CNC lathes to process various cold heading, bending and riveting parts.

[0005] Although the current C3601 lead brass material has cutting performance that meets the requirements for valve processing, there is a 2% cracking problem during cold heading and a 5% cracking problem during bending. Severely cracked valves are easily picked out during inspection, while slightly cracked ones are generally not easy to pick out. A few valves with poor bending are installed on tires, which affects the safety of vehicle driving.

[0006] The invention patent application with the publication number CN111304488A discloses a stress cracking resistant lead brass bar, characterized by comprising the following mass percentage composition, Cu: 58.0-60.0wt%, Pb: 0.8-1.9wt%, Fe: 0.10-0.20wt%, Ni: 0.5-2.0wt%, P: 0.003-0.02wt%, and the balance is Zn and inevitable impurities. The present invention adds Fe and Ni to the traditional lead brass, increases the proportion of α phase in the matrix, makes α phase and β phase exist as equiaxed crystals, makes the internal structure of the material more uniform, reduces stress concentration, and reduces the risk of cracking after welding.

[0007] The invention patent application with publication number CN111663063A discloses a lead brass bar suitable for high-speed automated processing, which includes the following components by weight percentage: Cu 57.5-59.5%, Pb 2.7-3.5%, Sn 0.01-0.3%, Fe 0.01-0.3%, other metal elements ≤0.3%, and the balance is zinc and unavoidable impurities; wherein the other metal elements are one or more of magnesium, calcium, cerium, and phosphorus; the present invention also provides a preparation method for the lead brass bar. The present invention produces a grain size of 5-15um, an α phase ratio of 65-85%, and a lead particle number greater than 12,000 / mm 2 Lead brass bars have excellent cutting performance and are suitable for automated, intelligent, high-speed and precise processing needs.

[0008] However, the anti-cracking performance of the brass disclosed in the above two patents during cold heading needs to be further improved. Therefore, in view of the above problems, the existing C3601 brass needs to be improved to solve the cold heading cracking and bending cracking problems that are easy to occur when the existing C3601 brass is used to process valves. Summary of the invention

[0009] The invention provides a lead brass having good performance of resisting cold heading cracking and bending cracking.

[0010] The invention provides a lead brass, wherein the lead brass comprises: Cu: 60.0-63.0wt%, Pb: 1.1-2.6wt%, Fe≤0.04wt%, Al≤0.06wt%, Sn≤0.1wt%, and the balance is Zn;

[0011] The microstructure of the lead brass includes twins, and the area of ​​the twins in the lead brass accounts for 15-30%.

[0012] Cu: The Cu content affects the ratio of α phase and β phase in brass structure. When the Cu content is lower than 60wt%, the ratio of β phase in brass increases significantly. β phase is a hard and brittle phase, which is easy to crack during valve bending. When the Cu content exceeds 63.0wt%, the ratio of β phase in brass room temperature structure gradually decreases, and finally becomes a single α phase structure. Due to the presence of Pb, it is very easy to crack during hot working due to the thermal brittleness of Pb.

[0013] Pb: Pb exists as an independent phase in brass, distributed as free particles at the grain boundary or within the grain. While improving the cutting performance of brass, it also reduces the plasticity of brass. The morphology, quantity and distribution ratio of the Pb phase also affect the cold heading performance of brass. With the increase of Pb content, the cutting performance of brass gradually improves. When the Pb content is lower than 1.1wt%, no matter how the Pb phase particles are refined, the number of Pb phase distribution per unit area will not exceed 9000 / mm2 , resulting in its cutting performance failing to meet the requirements of valve precision machining on the cutting performance of the material; when the Pb content exceeds 2.6wt%, the cutting performance of brass is not significantly improved, but excessive Pb content causes brass to become cold brittle and the cold heading performance of the material deteriorates, so in the brass of the present invention, the Pb content is controlled at 1.1-2.6wt%.

[0014] Fe: Excessive Fe will lead to excessive grain refinement, increasing the material's resistance to cold heading deformation. When the Fe content is below 0.04wt% in the alloy of the present invention, the effect on cold heading deformation is small.

[0015] Since Al and Sn, common impurity elements in lead brass, have a strong solid solution strengthening effect, which increases the hardness of brass and does not require cold heading deformation of the valve nozzle, the content of impurity elements Al and Sn in the lead brass of the present invention should be controlled below 0.06wt% and 0.1wt%, respectively.

[0016] Preferably, the structure of the lead brass further includes an α phase, and a β phase and a Pb phase located inside and at the boundary of the α phase, the area of ​​the β phase accounts for 3-8%, the average size of the Pb phase is ≤2.8 μm, and the distribution number of the Pb phase is ≥9000 / mm 2 .

[0017] The phase composition of the lead brass provided by the present invention also includes an α phase as a matrix phase, a β phase and a Pb phase uniformly distributed in the α phase and on the phase boundary, wherein the β phase area accounts for 3-8%, and if the β phase area accounts for a high proportion, the plasticity of the material deteriorates, and the material is prone to cracking during cold heading and bending; if the β phase area accounts for too little, the lead brass is prone to cracking during hot processing due to the thermal brittleness of Pb in the single-phase brass; the average size of the Pb phase is ≤2.8μm, and the distribution of the Pb phase is 9000 / mm 2 The above is because the finer the Pb particles, the more uniform the distribution, the smaller the impact on the plasticity of the Pb-containing brass matrix, and the smaller the negative impact on cold heading and bending. In addition, the number of Pb phase distribution also affects the cutting performance of lead brass. The more Pb phase distribution per unit area, the better the cutting performance of lead brass.

[0018] Further preferably, the content of Cu is 60-61wt%, the content of Pb is: 2.1wt%<Pb≤2.6wt%, the average size of the Pb phase is ≤2μm, and the number of Pb phases distributed is ≥14000 / mm 2 .

[0019] At a lower Cu content, the β phase area accounts for a higher proportion, and the β phase can dissolve more Pb than the α phase, and the undissolved Pb in the form of a single substance can reduce the negative impact on the cold heading and bending properties of the lead brass. At the same time, since the single substance Pb phase destroys the continuity of the brass matrix, the brass is easy to break chips during cutting, but it will cause the brass to crack easily during cold heading and bending. The present invention controls the average size of the Pb phase at a lower level, controls the distribution amount of the Pb phase at a higher level, and controls the Pb phase content at a higher level to ensure better cutting performance while improving the cold heading and bending properties of the lead brass.

[0020] Further preferably, the content of Cu is 61-62wt%, the content of Pb is: 1.6<Pb≤2.1wt%, the average size of the Pb phase is ≤2.5μm, and the number of Pb phases distributed is ≥12000 / mm 2 .

[0021] Further preferably, the content of Cu is 62-63wt%, the content of Pb is: 1.1<Pb≤1.6wt%, the average size of the Pb phase is ≤2.8μm, and the number of Pb phases distributed is ≥9000 / mm 2

[0022] When the Cu content increases appropriately, the area ratio of the β phase decreases, the Pb that can be dissolved in the β phase decreases, and the negative impact of the undissolved Pb in the form of a single substance on the cold heading and bending properties of the lead brass increases. At this time, the Pb content should be appropriately reduced to weaken this negative impact. Since the area ratio of the brittle β phase decreases, the average size of the Pb phase can be appropriately increased, that is, the upper limit of the average size of the Pb phase can be appropriately enlarged, and the distribution amount of the Pb phase can be appropriately reduced, that is, the lower limit of the distribution amount of the Pb phase can be appropriately enlarged, so that the obtained lead brass still has good cold heading performance, bending performance and cutting performance.

[0023] Preferably, the grain size of the lead brass is 25-45μm. Cold heading and bending deformation of metals occur due to the slippage of grains and the deformation of the grains themselves. If the grain size is too small, the number of grains will inevitably increase. Although the deformation can be evenly dispersed to each grain, it is not easy to form stress concentration, and thus the cracking tendency is small, but the smaller the grains, the more grains there are, which reflects a greater deformation resistance to the outside, and will make cold heading deformation difficult, increasing the tendency to crack; if the grain size exceeds 45μm, the grains are relatively coarse, and the bending part of the valve will appear orange peel when it is bent.

[0024] Preferably, the tensile strength of the lead brass is Rm: 370-420Mpa, the yield strength is Rp0.2: 270-340MPa, the hardness is HRB: 56-80, and the elongation is A: 15-28%. The yield strength, elongation and hardness can reflect the cold heading performance of the material. The lower the yield strength, the higher the elongation and the lower the hardness, the better the cold heading performance and bending performance of the material. However, as a valve, it is necessary to maintain a high strength to prevent deformation and leakage during service.

[0025] The invention also provides a method for preparing lead brass. The process flow of the preparation method comprises: smelting→horizontal continuous casting→extrusion→first drawing→annealing→second drawing.

[0026] Mixing and smelting the lead brass according to the mass percentage of each component;

[0027] The processing rate of the first drawing is 18-30%;

[0028] The annealing temperature is 450-560° C., and the insulation time is 90-300 min.

[0029] The present invention controls the processing rate of the first drawing to provide energy for forming twins while avoiding too small grains, and then obtains twins with a high proportion, a suitable Pb phase size and a grain size through a suitable annealing temperature and a holding time.

[0030] After the extruded billet is pickled, it is stretched to the intermediate specification through the first drawing, and the processing rate needs to be controlled at 18-30%. This is because the medium deformation is conducive to the formation of annealing twins. Corresponding to the lead brass of the present invention, when the disc-drawing processing rate is lower than 18% and higher than 30%, the proportion of twins appearing during annealing is small; in addition, when the processing rate is too low, the original grains of the extruded billet are unevenly broken, resulting in different sizes of annealing recrystallized grains. When the disc-drawing processing rate exceeds 30%, the original grains of the extruded billet are more fully broken, the annealing recrystallized grain size is less than 25μm, the deformation resistance increases during cold heading of the valve, and cracking is prone to occur.

[0031] The hard wire billet after stretching needs to be annealed to restore plasticity and obtain an appropriate amount of twins, as well as a suitable Pb phase size and grain size. The annealing temperature is 450-560°C, and the heating time from room temperature is 45-180 minutes. After reaching the set temperature, the holding time is 90-300 minutes. The wire billet after annealing is pickled to remove the surface oxide scale.

[0032] Preferably, the annealing temperature is 450-510°C, and the holding time is 120-210min. The present invention further controls the annealing temperature and holding time to minimize the fusion growth of the Pb phase, so that the Pb phase can better maintain the fine granularity of the extruded structure. If the annealing temperature is low, the recrystallized grain size is small, the average grain size is lower than 25μm, and the risk of cracking during cold heading and bending of the valve increases; if the annealing temperature is high, the average grain size and the size of the Pb phase will increase, the holding time is short, and the uniformity of the recrystallized grains is poor; if the holding time is long, the size of the Pb phase will gradually grow.

[0033] Preferably, the extrusion temperature is 620-720°C, the extrusion ratio is 50-300, and the extrusion speed is 4-16 mm / s. The present invention reduces the aggregation and growth of the Pb phase by controlling the extrusion temperature to obtain a Pb phase of appropriate size, and obtains a uniform and appropriate grain size by controlling the extrusion ratio and the extrusion speed.

[0034] Preferably, the ingot is heated to 620-720°C before extrusion for 20-60 minutes. The present invention controls the heating time and temperature before extrusion to reduce the fusion, aggregation and growth of Pb phase particles, thereby avoiding a significant reduction in the amount of Pb phase distribution in the extruded blank. The present invention uses an electromagnetic induction heating furnace for heating. Compared with other heating methods, induction heating can perform deep heating due to the large penetration depth of the current, which can shorten the heating time.

[0035] Further preferably, the brass extrusion of the present invention adopts an extrusion process with a relatively low temperature and a large extrusion ratio, the extrusion temperature is controlled at 620-690°C, the extrusion ratio is controlled at 200-300, and the extrusion speed is 8-13 mm / s. The purpose is to avoid the aggregation and growth of the Pb phase of the ingot structure by low-temperature heating, and the large extrusion ratio deformation can obtain uniform recrystallized grains. However, if the extrusion ratio is too high, after exceeding 300, the extruded recrystallized grains are small. Since the post-processing annealing of the present invention is not suitable for high-temperature annealing, the grain size of the finished product is difficult to control to the range of 25-45 μm.

[0036] Preferably, the smelting temperature is 1000-1090°C, and the insulation temperature is 1040-1080°C. The present invention prepares the ingredients according to the required components, smelts in an electric furnace, and the smelting temperature is 1000-1090°C. After all the metals are melted and the components are tested to be qualified, the molten copper is transferred to a insulation furnace at a insulation temperature of 1040-1080°C.

[0037] Preferably, the casting temperature of the horizontal continuous casting is 1040-1080°C, the pulling time is 1-7s, the pulling pitch is 1-10mm, the pause time is 0.1-3s, the reverse push time is 0.1-3s, the reverse pitch is 0.5-4mm, the retreat time is 0.1-3s, and the ingot sawing length is 550-1500mm. Before the horizontal continuous casting, the molten copper in the holding furnace solidifies through the crystallizer, and the horizontal method is to continuously pull the ingot.

[0038] Preferably, the processing rate of the second drawing is 7-16%. If the processing rate of finished products is lower than 7%, the tensile strength of the material is low; if the processing rate of finished products exceeds 16%, the plasticity of the wire is poor due to work hardening, and the valve is prone to cracking during cold heading and bending.

[0039] On the other hand, the present invention also provides an application of the lead brass in valve stems, relays, wiring terminals, connectors, cold-headed parts, bent parts and riveted parts.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The present invention controls the Cu content to limit the proportion of the β phase, thereby improving the plasticity of the lead brass and thus improving the cold heading cracking resistance and bending cracking resistance. At the same time, the Pb content is controlled to maintain the cutting performance of the lead brass while reducing the negative effects of the Pb element on cold heading and bending.

[0042] The present invention controls the lower limit of the proportion of twins so that lead brass has multiple slip system directions. During cold heading and bending, crystals are easy to slip, which improves the ductility of lead brass macroscopically and reduces the influence of Pb on cold heading and bending of lead brass. The present invention avoids the problem of increased plastic anisotropy of the alloy and reduced strength of the material by controlling the upper limit of the proportion of twins. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a metallographic structure photograph (200X) of the lead brass prepared in Example 1 of the present invention;

[0044] Figure 2 A metallographic structure photograph (200X) of the lead brass provided in Comparative Example 1 of the present invention;

[0045] Figure 3 This is a photo of a valve nozzle bent using the lead brass provided in Example 1 of the present invention;

[0046] Figure 4 This is a photo of the bending of a valve made of lead brass provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below with reference to the embodiments.

[0048] The present invention provides 3 embodiments and 6 comparative examples, and the specific components are shown in Table 1.

[0049] Example 1

[0050] A method for preparing a wire with a specification of Φ7.1 mm is as follows:

[0051] (1) Smelting: The materials are prepared according to the required ingredients and smelted in an electric furnace at a smelting temperature of 1000-1090°C. After all the metals are melted and the test results are qualified, the molten copper is transferred to a holding furnace at a holding temperature of 1045-1055°C.

[0052] (2) Horizontal continuous casting: The molten copper in the holding furnace solidifies through the crystallizer, and the ingot is pulled continuously in a horizontal manner. The ingot specification is Φ195 mm, the casting temperature is 1047-1060 ° C, the pulling length is 7 mm, the pulling time is 1 s, the pause time is 0.18 s, the reverse push length is 0.8 mm, the reverse push time is 0.25 s, the pause time after reverse push is 3.6 s, and the ingot sawing length is 700 mm.

[0053] (3) Extrusion: The Φ195mm*700mm ingot is heated to 660℃ in an electromagnetic induction heating furnace for 26 minutes. The heated ingot is extruded on a 2200T extruder with an extrusion ratio of 245. The extrusion billet specification range is At the same time, the extrusion flow number is 2, the extrusion speed is 9.6mm / s, and the wire is taken up in a coiling manner.

[0054] (4) First pulling: After the extruded billet is pickled to remove the oxide scale, it is stretched on the wire drawing machine to The processing rate is 25.4%.

[0055] (5) Annealing: The hard wire billet is annealed in an annealing furnace at a temperature of 470°C. The heating time from room temperature is 60 minutes. After reaching the set temperature, the insulation time is 180 minutes. The surface oxide scale of the wire billet after annealing is removed by pickling.

[0056] (6) Second drawing: after pickling The wire blank is stretched to the finished product specifications on the wire drawing machine The processing rate is 12.7%.

[0057] Example 2

[0058] A method for preparing a wire with a specification of Φ9.5mm is as follows:

[0059] (1) Smelting: The materials are prepared according to the required ingredients and smelted in an electric furnace at a smelting temperature of 1000-1090°C. After all the metals are melted and the test results are qualified, the molten copper is transferred to a holding furnace at a holding temperature of 1050-1060°C.

[0060] (2) Horizontal continuous casting: The molten copper in the holding furnace solidifies through the crystallizer, and the ingot is pulled continuously in a horizontal manner. The ingot specification is Φ254 mm, the casting temperature is 1045-1055 °C, the pulling length is 6.5 mm, the pulling time is 1 s, the pause time is 0.2 s, the reverse push length is 0.7 mm, the reverse push time is 0.2 s, the pause time after reverse push is 4 s, and the ingot sawing length is 800 mm.

[0061] (3) Extrusion: The Φ254mm*800mm ingot is heated to 680℃ in an electromagnetic induction heating furnace for 30min. The heated ingot is extruded on a 3150T extruder with an extrusion ratio of 276. The extrusion billet specification range is At the same time, the extrusion flow number is 2, the extrusion speed is 11.5mm / s, and the wire is taken up in a coiling manner.

[0062] (4) First pulling: After the extruded billet is pickled to remove the oxide scale, it is stretched on the wire drawing machine to The processing rate is 20.3%.

[0063] (5) Annealing: The hard wire billet is annealed in an annealing furnace at a temperature of 490°C. The heating time from room temperature is 70 minutes. After reaching the set temperature, the insulation time is 180 minutes. The surface oxide scale of the wire billet after annealing is removed by pickling.

[0064] (6) Second drawing: after pickling The wire blank is stretched to the finished product specifications on the wire drawing machine The processing rate is 9.8%.

[0065] Example 3

[0066] A method for preparing a wire with a specification of Φ5.92mm is as follows:

[0067] (1) Smelting: The materials are prepared according to the required ingredients and smelted in an electric furnace at a smelting temperature of 1000-1090°C. After all the metals are melted and the test results are qualified, the molten copper is transferred to a holding furnace at a holding temperature of 1060-1070°C.

[0068] (2) Horizontal continuous casting: The molten copper in the holding furnace solidifies through the crystallizer, and the ingot is continuously pulled horizontally. The ingot specification is Φ145 mm, the casting temperature is 1040-1050 °C, the pulling length is 9 mm, the pulling time is 1.2 s, the pause time is 0.15 s, the reverse push length is 0.55 mm, the reverse push time is 0.12 s, the reverse push pause time is 3 s, and the ingot sawing length is 550 mm.

[0069] (3) Extrusion: The Φ145mm*550mm ingot is heated to 630℃ in an electromagnetic induction heating furnace for 22 minutes. The heated ingot is extruded on a 1250T extruder with an extrusion ratio of 227. The extrusion billet specification range is At the same time, the extrusion flow number is 2, the extrusion speed is 8.4mm / s, and the wire is taken up in a coiling manner.

[0070] (4) First pulling: After the extruded billet is pickled to remove the oxide scale, it is stretched on the wire drawing machine to The processing rate is 23.4%.

[0071] (5) Annealing: The hard wire billet is annealed in an annealing furnace at a temperature of 450°C. The heating time from room temperature is 45 minutes. After reaching the set temperature, the insulation time is 210 minutes. The surface oxide scale of the wire billet after annealing is removed by pickling.

[0072] (6) Second drawing: after pickling The wire blank is stretched to the finished product specifications on the wire drawing machine The processing rate is 11.7%.

[0073] Comparative Example 1 is commercially available C3601 grade Wire.

[0074] Comparative Example 2: The Cu content and the Pb content are the same as those in Example 1, which do not meet the corresponding relationship between the Cu content and the average size of the Pb phase and the number of Pb phase distribution required by the present invention. The remaining components and the preparation process are the same as those in Example 1. The purpose is to compare the effects of the average size of the Pb phase and the number of Pb phase distribution on the processing properties of brass under the same Cu and Pb content conditions.

[0075] Comparative Example 3: The chemical composition is the same as that of Example 1. The ingot is heated in a gas furnace before extrusion for 180 min. The rest of the preparation process is the same as that of Example 1. The purpose is to compare the effects of ingot heating method and heating time on the microstructure and processing properties of brass.

[0076] Comparative Example 4: The chemical composition is the same as that of Example 1, the ingot extrusion temperature is 750°C, and the rest of the preparation process is the same as that of Example 1, the purpose is to compare the effect of ingot extrusion temperature on the microstructure and processing properties of brass.

[0077] Comparative Example 5: The chemical composition is the same as that of Example 1, the first drawing processing rate of the extruded billet is 10%, and the rest of the preparation process is the same as that of Example 1, the purpose is to compare the effect of the drawing processing rate of the extruded billet on the microstructure and processing performance of brass.

[0078] Comparative Example 6: The chemical composition is the same as that of Example 1, the annealing temperature of the extruded billet after the first drawing is 600°C, and the rest of the preparation process is the same as that of Example 1, the purpose is to compare the effect of the annealing temperature after the first drawing of the extruded billet on the microstructure and processing properties of brass.

[0079] The following tests were performed on the microstructures of the three embodiments and six comparative examples, and the results are recorded in Table 5.

[0080] The grain size, twin area ratio, β phase area ratio, Pb phase size and Pb phase distribution quantity were observed under a microscope, and the results are shown in Table 2.

[0081] The following performance tests were performed on the three embodiments and six comparative examples, and the results are recorded in Table 6.

[0082] Tensile strength, yield strength Rp0.2 and elongation: tested in accordance with GB / T228.1~2021 "Tensile test of metallic materials Part 1: Room temperature test method".

[0083] Hardness HRB: Tested according to GB / T4340.1~2009 "Rockwell hardness test for metallic materials Part 1: Test method".

[0084] Performance Analysis:

[0085] Cutting performance: reflected by copper chip morphology and cutting index. After the cutting process, copper chips are collected and the cutting performance is compared by the morphology of the copper chips. The finer the copper chips, the better the cutting performance.

[0086] like Figure 1 As shown, the metallographic structure of the lead brass prepared in Example 1 is uniform and consistent, with an average grain size of 27.5 μm. A large number of twins can be seen in the structure, and the twin area accounts for 18.81%. The black dots in the figure are β phases, accounting for 5.80% of the area. After the sample is corroded, the Pb phase is not visible.

[0087] like Figure 2 As shown, the lead brass provided in Comparative Example 1 has uniform metallographic structure, small grains, an average grain size of 15.3 μm, and only a very small amount of twins, with the twin area accounting for only 0.42%. The black blocks are β phases, which are relatively large in number and account for 11.08% of the area. After the sample is etched, the Pb phase is not visible.

[0088] from Figure 3 and Figure 4As shown, the 90° bend of the valve nozzle made of the lead brass provided in Example 1 is smooth and crack-free, while the 90° bend of the valve nozzle made of the lead brass provided in Comparative Example 1 is cracked. The specific data of the mechanical properties of the lead brass prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 are shown in Table 3. It can be seen from Table 3 that the comprehensive mechanical properties of Examples 1-3 of the present invention are better.

[0089] 10,000 valves were processed, and the proportions of cold heading cracking, bending cracking, and bending orange peel were counted. The copper chips of Example 1 were finer than those of HPb63-3. The cutting force was calculated by the cutting force tester and compared with that of HPb63-3, and then according to the formula: The cutting performance index was obtained and the results were recorded in Table 4. It can be seen from Table 4 that the valve cold heading performance and bending performance of the lead brass provided by Examples 1-3 of the present invention are higher, the bending orange peel ratio is lower, and the cutting performance is better, while the above performance of the lead brass provided by Comparative Examples 1-6 is poor.

[0090] As shown in Table 2, the embodiments of the present invention provide suitable grain size, higher area ratio of twin area, lower average size of Pb phase, higher number of Pb phase distribution, and when the area ratio of β phase is large, the present invention ensures that the prepared lead brass has higher cold heading performance and bending performance by regulating the average size of Pb phase and the number of Pb phase distribution.

[0091] Table 1 Composition / wt% of the Examples of the present invention and the Comparative Examples

[0092]

[0093] Table 2 Microstructure of the embodiments of the present invention and the comparative examples

[0094]

[0095]

[0096] Table 3 Performance of the embodiments of the present invention and the comparative examples

[0097]

[0098] Table 4 Cold heading and bending performance test results of the embodiments of the present invention and the comparative examples

[0099]

Claims

1. A lead brass, characterized in that: The lead brass has a mass percentage composition of: Cu: 60.0-63.0wt%, Pb: 1.1-2.6wt%, Fe≤0.04wt%, Al≤0.06wt%, Sn≤0.1wt%, and the balance is Zn; The microstructure of the lead brass includes twins, and the area of ​​the twins in the lead brass accounts for 15-30%.

2. The lead brass according to claim 1, characterized in that: The structure of the lead brass also includes an α phase, and a β phase and a Pb phase located inside and at the boundary of the α phase. The area of ​​the β phase accounts for 3-8%, the average size of the Pb phase is ≤2.8 μm, and the distribution number of the Pb phase is ≥9000 / mm 2 .

3. The lead brass according to claim 2, characterized in that: The content of Cu is 60-61wt%, the content of Pb is: 2.1wt%<Pb≤2.6wt%, the average size of Pb phase is ≤2μm, and the number of Pb phase distribution is ≥14000 / mm 2 .

4. The lead brass according to claim 2, characterized in that: The content of Cu is 61-62wt%, the content of Pb is: 1.6<Pb≤2.1wt%, the average size of Pb phase is ≤2.5μm, and the number of Pb phase distribution is ≥12000 / mm 2 .

5. The lead brass according to claim 2, characterized in that: The content of Cu is 62-63wt%, the content of Pb is: 1.1<Pb≤1.6wt%, the average size of Pb phase is ≤2.8μm, and the distribution number of Pb phase is ≥9000 / mm 2 .

6. The lead brass according to claim 1, characterized in that: The grain size of the lead brass is 25-45 μm.

7. A method for preparing lead brass, characterized in that: The process flow of the preparation method includes: smelting→horizontal continuous casting→extrusion→first drawing→annealing→second drawing; Mixing and smelting the lead brass according to the mass percentage of each component as described in any one of claims 1 to 6; The processing rate of the first drawing is 18-30%; The annealing temperature is 450-560° C., and the insulation time is 90-300 min.

8. The method for preparing lead brass according to claim 7, characterized in that: The annealing temperature is 450-510° C., and the insulation time is 120-210 minutes.

9. The method for preparing lead brass according to claim 7, characterized in that: The extrusion temperature is 620-720° C., the extrusion ratio is 50-300, and the extrusion speed is 4-16 mm / s.

10. The method for preparing lead brass according to claim 9, characterized in that: The extrusion temperature is 620-690°C, the extrusion ratio is 200-300, and the extrusion speed is 8-13 mm / s.

11. The method for preparing lead brass according to claim 7, characterized in that: The ingot is heated to 620-720°C before extrusion, and the heating time is 20-60 minutes.

12. Use of the lead brass according to any one of claims 1 to 6 in valves, relays, wiring terminals, connectors, cold-headed parts, bent parts and riveted parts.

Citation Information

Patent Citations

  • Stress cracking resisting lead brass bar and preparing method thereof

    CN111304488A

  • Lead brass bar suitable for being processed at high speed automatically and preparation method thereof

    CN111663063A